LQFM184: A Novel Wide Ultraviolet Radiation Range Absorber Compound - Vinhal, Daniela C.; Ivan de Avila, Renato; Rodrigues, Thaisangela L.; Silva, Andressa K.; Moreira, Larissa C.; Valadares, Marize C.; Luzin, Rangel M.; Liao, Luciano M.; Gil, Eric de S.; Vaz, Boniek G.; Assis, Rogerio J.; Goncalves, Pablo J.; et al. (Wiley-Blackwell, 2020)
The use of sunscreen has become an indispensable daily routine since UV radiation is a critical environmental stress factors for human skin. This study focused on the design, synthesis, thermal/chemical stability and efficacy/safety evaluations of a new heterocyclic derivative, namely LQFM184, as a photoprotective agent. The compound showed stability when submitted under oxidative and high-temperature conditions. It also revealed an absorption at 260-340 nm (UVA/UVB), with a main band at 298 nm and a shoulder close to 334 nm. LQFM184 showed capacity to interact with other existing UV filters, promoting an increase in the sun protection factor. In relation to acute toxicity, its estimated LD50 was >300-2000 mg kg(-1), probably with a low potential of inducing acute oral systemic toxicity hazard. In addition, our data showed that this compound did not have eye irritation, skin sensitization or phototoxicity potentials. Taken together, these findings make LQFM184 a promising ingredient to be used, alone or in association with other UV filters, in cosmetic products such as sunscreens with a broad spectrum of protection.